Studies on Homalomeneae (Araceae) of Sumatera II: Homalomena limnogena, a novel species from Pulau Belitung, and the first record of colonial helophytism in the Homalomena Chamaecladon Supergroup - Peter C., Boyce; Sin Yeng, Wong (Taylor & Francis Ltd., 2013)
A diminutive colonial helophytic species of Homalomena, Homalomena limnogena P.C. Boyce and S.Y. Wong sp. nov, is described as new to science from Pulau Belitung, Sumatera, and assigned to the Chamaecladon Supergroup. Homalomena limnogena is only the third helophytic species recorded for the genus, and is the first record of colonial helophytism in the Chamaecladon Supergroup. Homalomena limnogena very likely represents a third separate evolution of this life form for the genus Homalomena. A key to helophytic Homalomena species is provided and the new species is illustrated.